THE IMPACT OF THE COVID PANDEMIC 19 IN THE IMPLEMENTATION OF THE PKN SUBJECT CURRICULUM IN SMAN 2 TAPAKTUAN - Lahmuddin Lubis; Suharian Amiril Akbar; Muhammad Yusuf Siregar (Universitas Dharmawangsa, 2020)
The implementation of the curriculum is an effort or application of a curriculum that has been designed or designed. In implementing the 2013 curriculum learning PKN subjects, teachers are required to understand the characteristics, concepts, learning objectives, implementation strategies, basic competency maps, core competencies, determining topics, and elaborating basic competencies into indicators that must be achieved by students. This research is a descriptive study with a qualitative approach. Data collection through interviews, observation, and documentation. The results of the discussion showed that the impact of the 19th pandemic on the implementation of the 2013 curriculum in PKN subjects greatly affected teachers and students. The teacher becomes more difficult in formulating learning activities. Apart from the 2013 curriculum they are still not too well mastered and added to the conditions of distance learning that encounter many obstacles